Miłosz w sporze z formą poetycką - Kluba, Agnieszka (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
Czesław Miłosz accompanied his poetry with an extensive body of self-reflective writings, developed over many years. It is characterised by, on the one hand, a relative constancy of recurring motifs, and on the other, an equally constant tendency to juxtapose the motifs in variously defined binary systems. The analysis of connections that occur not so much between the elements of specific antinomies, but, on a higher level, between separate antinomies (especially between values ascribed to poles of the oppositions), makes it possible to notice that many of the antinomies cannot be subjected to easy reconciliations, but rather exclude each other. This makes it possible to understand why Miłosz’s thought seems to be systematic. Above all, however, it allows us to look, in a new way, at the feats of Miłosz’s constant struggle against poetic form – immanent contradictions and inconsistencies of Miłosz’s reflection become interesting only when they are referred to the order of creation and its disturbing metamorphoses.